Deutschlands hohe Ungleichheit verursacht wirtschaftlichen Schaden - Marcel Fratzscher (Wirtschaftsdienst, 2016)
– "Welfare for everyone", according to former chancellor and economics minister Ludwig Erhard, has been the credo of Germany's economic and social policy for the past 60 years. However, Germany is increasingly failing to achieve this objective. Germany is a country of enormous inequality - income, wealth and opportunities are distributed more unequally in Germany than in almost any other industrialised country. This inequality imposes huge economic costs for Germany, as evidenced by lower economic growth and declines in other indicators of well-being. And it has triggered a harmful fight among groups of society for public resources. This fight will further intensify with the dramatic changes Germany is currently undergoing, from demographic change to globalisation to the migration challenge. The main culprit for the high and rising inequality is not a lack of public redistribution of income and wealth, but rather the unusually high inequality of opportunity, through which an ever higher share of citizens is deprived of the chance to develop and use their talents and skills. Such barriers have become massive, beginning already in early childhood.
Keywords: D3; O52; 330; Verteilungsgerechtigkeit; Verteilungspolitik; Verteilungskonflikt; Bildungschancen; Deutschland